Early and sustained improvements of lung clearance index from two to sixteen weeks of elexacaftor/tezacaftor/ivacaftor therapy in patients with cystic fibrosis—a real world study - Appelt, Dorothea; Steinkamp, Gratiana; Sieber, Sarah; Ellemunter, Helmut (Frontiers in Pharmacology, 2023)
Since the introduction of CFTR modulator therapies, longitudinal real-life data of lung clearance index (LCI) during treatment is scarce. In this single-centre, post-approval setting, we report data of 51 patients with different stages of lung disease, age 2-52 years with repeated measurements of forced expiratory volume as a percentage of the predicted value (ppFEV₁) and LCI after 2, 4 and 16 weeks of CFTR modulator treatment and at baseline. In 25 patients during elexacaftor/tezacaftor/ivacaftor (ELX/TEZ/IVA) treatment, significant improvements of LCI (median -1.4) and ppFEV₁ (median +8.3%) were observed after only two weeks, and were maintained after 4 and 16 weeks of treatment (LCI: -2.0, -2.2; ppFEV₁: +7.2%, +11.8%). We observed a significant correlation between LCI improvement at week 16 and lower baseline LCI. In 26 younger and healthier patients receiving lumacaftor/ivacaftor (LUM/IVA) treatment, no significant changes of LCI and ppFEV₁ occured. With ELX/TEZ/IVA, our data shows rapid, significant improvements of LCI and ppFEV₁ already after 2 weeks. Early LCI measurements can help to assess the patient’s response to this high-cost therapy.